2012
DOI: 10.1002/ajmg.a.35601
|View full text |Cite
|
Sign up to set email alerts
|

Opposing phenotypes in mice with Smith–Magenis deletion and Potocki–Lupski duplication syndromes suggest gene dosage effects on fluid consumption behavior

Abstract: A quantitative long-term fluid consumption and fluid licking assay was performed in two mouse models with either an ~ 2Mb genomic deletion, Df(11)17, or the reciprocal duplication CNV, Dp(11)17, analogous to the human genomic rearrangements causing either Smith-Magenis syndrome [SMS; OMIM #182290] or Potocki-Lupski syndrome [PTLS; OMIM #610883], respectively. Both mouse strains display distinct quantitative alteration in fluid consumption compared to their wild-type littermates; several of these changes are di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Animal models with reciprocal deletions and duplications can inform dosage‐dependent phenotypes associated with a particular CNV . The 16p11.2 CNV mouse models demonstrate dosage‐dependent changes in gene expression, viability, brain architecture, and behavior, with the deletion being more severe than the duplication .…”
Section: Downstream Mechanisms: From Cnv To Phenotype and Beyondmentioning
confidence: 99%
See 2 more Smart Citations
“…Animal models with reciprocal deletions and duplications can inform dosage‐dependent phenotypes associated with a particular CNV . The 16p11.2 CNV mouse models demonstrate dosage‐dependent changes in gene expression, viability, brain architecture, and behavior, with the deletion being more severe than the duplication .…”
Section: Downstream Mechanisms: From Cnv To Phenotype and Beyondmentioning
confidence: 99%
“…68,69 Recurrent deletion and duplication syndromes, as defined above, can either manifest with similar characteristics or with mirror image traits, that is, phenotypic extremes such as macrocephaly vs microcephaly at the 16p11.2 and 1q21.1 loci, or high vs low body mass index at the 17p11.2 locus. 22,[70][71][72][73] The dosage-sensitive gene has been identified in several genomic disorders and recurrent microdeletion/microduplication syndromes (see eg, Table 2). In other cases, a dosage-sensitive gene has been associated with a specific aspect of a mirror trait-for example, KCTD13 and head circumference size at the 16p11.2 locus (Table 3).…”
Section: Dosage Sensitivity: Haploinsufficiency and Triplosensitivitymentioning
confidence: 99%
See 1 more Smart Citation
“…b). Even complex behaviors, as exemplified by “licking behavior” in mice “could be shown to objectively and quantitatively manifest as mirror traits in these del/dup CNV animal models [Heck et al, ]. This was of interest given that the PTLS duplication was initially reported in association with autism in some patients [Potocki et al, ] and objectively found in 11 of 15 subjects tested [Treadwell‐Deering et al, ].…”
Section: Mirror Traitsmentioning
confidence: 99%
“…Many of these behavioral phenotypes are reciprocal or opposing to those seen in Df(11)17/+ mice, underscoring the dosage-sensitive nature of these disorders [109]. For example, a recent study investigating cerebellum-driven licking behavior in Dp(11)17/+ and Df (11)17/+ mice found that many of the quantitative licking behavior parameters analyzed were altered in a directly-opposing manner [110]. Specifically, the interval between visits to the waterspout, number of licks per visit, and variability in the number of licks per lick-burst were all altered in duplication and deletion animals in opposite directions compared to wild-type mice (ex: longer versus shorter intervals, etc).…”
Section: Modeling Sms and Ptls In Rodentsmentioning
confidence: 99%